Linear and Nonlinear Dynamic Model of a Gantry Crane System - Hazriq Izzuan, Jaafar; Mohd Ashraf, Ahmad; Rozaida, Ghazali; A. M., Kassim (Centre for Advanced Research on Energy (CARe), 2016)
This paper investigates linear and nonlinear dynamic models for a Gantry Crane System (GCS). The system is a Single Input Multi Output (SIMO) system which a trolley displacement and payload oscillation as the outputs. The GCS is modeled by using the Lagrange Equation and both system responses are observed and analysed. The fundamental differences between the linear and nonlinear equations are presented. This analysis is beneficial for the development of efficient controllers for a GCS.